TEST INSTRUMENT DEVELOPMENT WITH LOCAL WISDOM CONTEXT ASSISTED BY THE ISPRING APPLICATION IN MATHEMATICS COURSE - Nur, Fitriani; Makmur, Firdayana; Fajriah, Nurul Ainun (IAIN Ambon, 2025)
While online learning continues to expand, there remains a lack of reliable evaluation tools to accurately assess students' mathematical abilities. This study aims to address this gap by developing a test instrument, supported by the iSpring application, to effectively measure these abilities. This study falls under the category of 'Research and Development' (R&D), a systematic process aimed at creating and testing innovative solutions to address specific challenges within the field of education. The research instruments consist of validity sheets, lecturers, student response questionnaires, and tests. An analysis of the expert assessment sheets was then carried out, including an analysis of the responses of students and lecturers, the validity of the questions, the reliability test, the level of difficulty test, and the different tests of the questions. The development process followed four stages: preliminary analysis, self-evaluation, prototyping, and field testing. The resulting instrument demonstrated high validity and reliability, was categorized as practical, and consisted of items with an easy difficulty level and moderate discrimination power. Meanwhile, the average mathematics ability of students is in the moderate category.